Influence of Ghrelin and Adipocytokines on bone mineral density in adolescent female athletes with amenorrhea and eumenorrheic athletes - Russell, M.; Misra, M. (Cytokines, growth mediators and physical activity in children during puberty, 2010)
Adolescent female athletes are at increased risk for low bone mineral density (BMD) secondary to exercise-induced hypogonadism. Of particular concern is that the adolescent years are also a critical time for bone accrual, and deficits incurred during this period could lead to suboptimal peak bone mass acquisition and subsequent fracture risk in later life. Although weight-bearing exercise is typically associated with an increase in BMD, amenorrheic athletes have lower BMD than eumenorrheic athletes and nonathletic controls as a consequence of low energy availability and subsequent hypogonadism. It is important to recognize that critical interactions exist between net energy availability and the hypothalamo-pituitary-gonadal (H-P-G) axis that are key to the development of a hypogonadal state when energy intake cannot keep pace with expenditure. While the link between energy availability and gonadtotropin pulsatility patterns is well established, the actual metabolic signals that link the two are less clear. Decreased energy availability in athletes is associated with decreases in fat mass, and alterations in adipokines (such as leptin and adiponectin) and fat-regulated hormones (such as ghrelin and peptide YY). These hormones impact the H-P-G axis in animal models, and it is possible that in athletes alterations in fat-related hormones signal the state of energy availability to the hypothalamus and contribute to suppression of gonadotropin pulsatility, hypothalamic amenorrhea and consequent decreased BMD. A better understanding of pathways linking low energy availability with functional hypothalamic amenorrhea and low BMD is critical for the development of future therapeutic strategies addressing these issues in amenorrheic athletes.